The role of circulating fibrocytes in inflammation and autoimmunity. Issue 1 (1st January 2013) - Galligan, Carole L.; Fish, Eleanor N.
Abstract : Review on the role of circulating fibrocytes in augmenting the inflammatory/immune processes, and contributing to tissue remodeling in autoimmune diseases. Abstract : Autoimmunity is a chronic process resulting in inflammation, tissue damage, and subsequent tissue remodeling. Circulating fibrocytes are bone marrow‐derived cells with characteristics of hematopoietic and mesenchymal cells. These cells have been implicated in many inflammatory and fibrotic conditions as well as in wound healing. Fibrocytes can amplify the inflammatory/immune response through multiple mechanisms, including antigen presentation, cytokine and chemokine secretion, and production of MMPs. Increased numbers of circulating fibrocytes are observed in RA, systemic scleroderma, and Gravesˈ disease. Here, we review the current literature and potential involvement of fibrocytes in inflammation and autoimmunity.